If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(5x + -50) = 0 Reorder the terms: 9(-50 + 5x) = 0 (-50 * 9 + 5x * 9) = 0 (-450 + 45x) = 0 Solving -450 + 45x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '450' to each side of the equation. -450 + 450 + 45x = 0 + 450 Combine like terms: -450 + 450 = 0 0 + 45x = 0 + 450 45x = 0 + 450 Combine like terms: 0 + 450 = 450 45x = 450 Divide each side by '45'. x = 10 Simplifying x = 10
| A=4*3.14r | | 1/5*(-10)-2 | | 2x+1+6x=73 | | A=1/2(b+c) | | 35=-3x+13x-62 | | -4-2x=-26 | | 57=3x+6x+3 | | Y+6/5=Y+8/7 | | 1-0.4k=1 | | -6.4=-2.5tx | | 5a+2b=30 | | X-5*(-2)=-1 | | a-5=-24 | | -3+3=5s+21 | | -2a+21+6a=4a-7a | | 2*6=14-y | | ax+b=cx+2 | | 2x=14-(-2) | | 10x-19x=6x+1 | | 8+x/9=7 | | 4x-5x+20=-2 | | (x^2-3x+2)x=2184 | | -2x-2x=35-7 | | 12g+31h=-8g | | 0.4(7+2x)+1.1x=3.1 | | -9=4x-11 | | 4*-4+2*-2=-20 | | 12.25=0.25x+9 | | x^3-3x^2+2x=2184 | | 5/y+3/x | | 4(2a-1)-4= | | 3*-4+5*-2=-22 |